Inter Agency Collaboration in Poverty Alleviation: A Public Administration Perspective - Sa’adih, Sa’adih; Hutauruk, Rosinta Paulina; Lauravia, Dyah (JURNAL SOSIAL DAN HUMANIS SAINS, 2023)
This study explores the dynamics of inter-agency collaboration in poverty alleviation programs within the context of public administration in Indonesia. Recognizing the multidimensional nature of poverty, the research investigates how various government institutions coordinate efforts to deliver more integrated and effective services. Using a qualitative case study approach, the study analyzes institutional practices, coordination mechanisms, and challenges encountered in selected regions. Findings reveal that effective collaboration is facilitated by leadership commitment, clear role division, shared goals, and adaptive governance structures. However, several barriers persist, including bureaucratic fragmentation, lack of integrated data systems, resource asymmetry, and limited community engagement. The study emphasizes that successful inter-agency collaboration not only improves policy coherence and service delivery but also enhances public value through inclusivity and efficiency. These insights contribute to the discourse on collaborative governance in public administration and offer policy recommendations for strengthening institutional synergy in poverty alleviation efforts.